Performance Studies of a Triple Concentric Helical Tube Heat Exchanger using Al2O3 Nano-Fluid - N Das, S; P Jena, S; Panigrahi, S; K Mohanty, U; M Behera, V (International Journal of Engineering and Technology, 2018)
A triple tube concentric type heat exchanger was selected for the analysis of heat exchanger characteristics. The heat exchanger was provided with a helical coil over the middle flow pipe. The heat exchanger characteristics were studied under turbulent flow conditions for the N-H-C and C-H-Nconfigurations of flow separately. Al2O3 Â nano-particles of approximated size of 50 nm were used to constitute the Al2O3 nano- fluid which was employed to enhance the effectiveness of the heat exchanger with both parallel and counter flow patterns. In the N-H-C configuration flow of nano-fluid at normal temperature took place in the inner pipe while the cold fluid flows in the annulus region and hot fluid was made to flow through the helical coil over the inner pipe.in C-H-Nconfiguration normal ,cold and hot fluid flowed in the- annulus region, inner and the helical coil respectively.the analysis revealed that the N-H-C flow arrangement was more effective in the transfer of heat to that for the C-H-Nflow arrangement. Also it was observed that with insertion of the helical coil and the use of nano-fluid enhance the effectiveness of heat exchanger.Â Â Â Â